(x+2y-1)dx-(x+2y-5)dy=0

Subscribe to MATHalino on

- Tapered Beam
- Vickers hardness: Distance between indentations
- Time rates
- Minima Maxima: y=ax³+bx²+cx+d
- Make the curve y=ax³+bx²+cx+d have a critical point at (0,-2) and also be a tangent to the line 3x+y+3=0 at (-1,0).
- Minima maxima: Arbitrary constants for a cubic
- Minima Maxima: 9a³y=x(4a-x)³
- Minima maxima: a²y = x⁴
- how to find the distance when calculating moment of force
- strength of materials
- Analytic Geometry Problem Set [Locked: Multiple Questions]
- Equation of circle tangent to two lines and passing through a point
- Product of Areas of Three Dissimilar Right Triangles
- Perimeter of Right Triangle by Tangents
- Differential equations
- Laplace
- Families of Curves: family of circles with center on the line y= -x and passing through the origin
- Family of Plane Curves
- Differential equation
- Differential equation

Home • Forums • Blogs • Glossary • Recent

About • Contact us • Disclaimer • Privacy Policy • Hosted by WebFaction • Powered by Drupal

About • Contact us • Disclaimer • Privacy Policy • Hosted by WebFaction • Powered by Drupal

Forum posts (unless otherwise specified) licensed under a Creative Commons Licence.

All trademarks and copyrights on this page are owned by their respective owners. Forum posts are owned by the individual posters.

All trademarks and copyrights on this page are owned by their respective owners. Forum posts are owned by the individual posters.

What do you need to do with this equation? You just write the equation but there is no instruction.

Can i solve this using homo? Our professor only gave that equation and nothing else.

Nope use suggested substitution method. since the linear equation is parallel, then use u = x + 2y

$$(x+2y-1)dx-(x+2y-5)dy=0$$

Let $u = x + 2y - 1 \rightarrow du = dx + 2dy$ which gives $dx = du - 2dy$

Substituting to the equation

$$\begin{eqnarray}

u(du - 2dy) - (u - 4)dy &=& 0\\

u du - (3u - 4)dy &=& 0\\

\dfrac{udu}{3u-4} - dy &=& 0\\

\dfrac{1}{3} \left(1 - \dfrac{4}{3u - 4}\right)du - dy &=& 0\\

\displaystyle{\int \dfrac{1}{3} \left(1 - \dfrac{4}{3u - 4}\right)}du - \int dy &=& C\\

\dfrac{1}{3}u - \dfrac{4}{3} \ln|3u - 4| - y &=& C\\

u - 4 \ln|3u - 4| - 3y &=& C\\

4 \ln|3u - 4| &=& u - 3y + C\\

4 \ln|3(x + 2y - 1) - 4| &=& x + 2y - 3y + C\\

4 \ln|3x + 6y - 7| &=& x - y + C\\

3x + 6y - 7 &=& Ce^{\frac{x-y}{4}} (ANSWER)

\end{eqnarray}$$

P.S. There can also be other forms of the general solution